Tinjauan Meta analisis: Apakah PBL berpengaruh terhadap kemampuan matematika siswa SMP? - Bahar, Rosid; Retnawati, Heri; Hidayat, Opik; Sudarna, Nanong (Program Studi Pendidikan Matematika, Universitas Nusantara PGRI Kediri, 2024)
This research aims to measure the mathematics abilities of junior high school students using the Problem Based Learning (PBL) learning model. The research method used is descriptive quantitative using meta analysis. The research mapped was obtained from journal articles, theses, theses and dissertations published between 2010 and 2020 with the help of publish or perish software as an article collection application. The research article meta-analysis technique uses the JASP 0.14.1.0 application to further interpret the heterogeneity, aggregate, bias detection, forrest and funnel plot tests. The results of the research show that the mathematics ability of Indonesian junior high school students is 74 on a scale of 0 -100. This aggregate was obtained from heterogeneous previous research results with a high category deviation index which is possible for bias. Strengthening bias was also obtained from the Rank correlation test and Regression test for Funnel plot asymmetry (